2021
DOI: 10.1186/s12967-020-02638-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune landscape and prognostic immune-related genes in KRAS-mutant colorectal cancer patients

Abstract: Background KRAS gene is the most common type of mutation reported in colorectal cancer (CRC). KRAS mutation-mediated regulation of immunophenotype and immune pathways in CRC remains to be elucidated. Methods 535 CRC patients were used to compare the expression of immune-related genes (IRGs) and the abundance of tumor-infiltrating immune cells (TIICs) in the tumor microenvironment between KRAS-mutant and KRAS wild-type CRC patients. An independent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 67 publications
3
35
0
1
Order By: Relevance
“…Moreover, some chemokine receptors have the potential to be drug targets in various diseases. 25 , 26 GIMAP7 is associated with the cytokine receptor interaction pathway, indicating its role in the induction of immune cell recruitment. Therefore, the intervention of GIMAP7 expression could impact the tumour immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some chemokine receptors have the potential to be drug targets in various diseases. 25 , 26 GIMAP7 is associated with the cytokine receptor interaction pathway, indicating its role in the induction of immune cell recruitment. Therefore, the intervention of GIMAP7 expression could impact the tumour immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients with CRC, except for those with high levels of microsatellite instability (MSI) or deficient mismatch repair (dMMR), cannot therapeutically benefit from immunotherapies because they have low immunogenicity [ 125 127 ]. Furthermore, recent studies have shown that KRAS -mutant CRC have significantly reduced infiltration of naïve B cells, macrophage M1, activated CD4 T cells, cytotoxic cells and neutrophils, and obviously increased regulatory T cells compared to patients with KRAS wild-type CRC [ 128 , 129 ]. Besides, multiple immune-related pathways are down-regulated in KRAS -mutant CRC, such as the interferon-γ (IFN-γ) pathway [ 129 ].…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…For a reliable immune assessment, we used the TIMER algorithm to analyze immune scores and visualized them with the R “ggplot2” and “pheatmap” packages ( Newman et al, 2015 ; Becht et al, 2016 ; Li et al, 2016 ; Aran et al, 2017 ; Racle et al, 2017 ; Finotello et al, 2019 ; Sturm et al, 2019 ; Hu et al, 2020 ; Li et al, 2020 ; Liu et al, 2021 ). Next, we analyzed the infiltration of six immune cells using the TIMER 9 (tumor immune estimation resource) online tool.…”
Section: Methodsmentioning
confidence: 99%